Synthesis and characterization of copper oxide/porous silicon composite for photodetector applications - Al-Jumili, Batool Eneaze Bandar (2017)
Copper oxide/porous silicon (CuO/PS) nanocomposites has been synthesized by a combined electrochemical etching and pulse laser ablation (PLA) techniques. The objective of this study is to enhance the photoluminescence (PL) efficiency and stability of luminescence porous silicon produced by electrochemical etching technique via incorporation of copper within it. The strategy is based on a simple well-known assumption that transition metal can be easily introduced inside of silicon (Si) band gap as impurity levels. Consequently, the numbers of carrier will be increased and affect electronic properties that will promote good PL efficiency. This study presents three steps to prepare CuO/PS nanocomposites. Firstly, the preparation of aqueous solution contains Cu species by laser ablation of Cu target. The laser ablation mechanism of copper target in pure distilled water and the effect of ablation time factor were investigated. Results from the experiments undertaken for this purposed show that the shape of the NPs was quasi-spherical. This has been attributed to the diffusion of oxygen in the solution. Further observation found that the NPs size decreased and the size distribution become narrow as the ablation times increase. This is due to the prolonged interaction of ablated NPs with laser beam that led to the fragmentation of bigger NPs into smaller ones. The second step introduced the preparation of porous silicon by electrochemical etching of a commercial n-type silicon wafer. The control of the size and the shape of the porous Si structures were investigated by modifying several etching parameters, which were current density, etching time, and electrolyte concentration. The surface morphologies of PS confirm that pore diameter and nanostructure are dependent on the etching parameters, and that the shifting towards shorter wavelength is due to the diminishing of the silicon skeletons (quantum confinement) where blue shift of wavelength increases along with porosity. Gravimetrical method was used to determine the porosity percentage of the samples. According to the quantum confinement luminescence model, the shorter peak wavelength of luminescence has caused the increase in the energy band gap (Eg) of the PS. The third step was to integrate the yield of pulse laser ablation and electrochemical etching to produce CuO/PS nanocomposites with highly consistent shape and structure. The control of the geometry of the nanostructures was investigated by modifying several deposition parameters that included solution concentration, deposition time, current density and post-annealing temperature. The surface morphologies of CuO/PS verify that the nano-dendrite (NDs) structures are dependent on the deposition parameters, as well the copper phases, including Cu, CuO and Cu2Othat deposited on the PS layer. The PL exhibited an enhanced peak with narrow line. Metal-Semiconductor-Metal (MSM) photodetectors based on PS/Si and CuO NDs/PS heterojunctions were then fabricated. Current-voltage (I-V) measurements were performed for both photodetectors under light and dark conditions. The diode behavior of the CuO nanodendrite/PS device was prominently superior compared to the PS/Si device where the contrast ratio was 63 and 3, respectively. The sensitivity of the CuO NDs/PS device increases to 660% as a function of time and becomes much higher compared to the PS/Si device (180%). The photoresponsivity of the CuO/PS detector was 500 mA/W, which is almost 2-fold higher than that of PS/Si detector. This result could be attributed to enhance surface area to volume ratio due to the three dimensional nature and high crystal quality of the CuO dendrite layer. The larger surface to volume ratio of the CuO dendrite enables the CuO dendrite device to collect more light, thereby increasing the photocurrent. In addition, the high quality of CuO dendrite decreases the density of trapping centers of charge caused by defects and therefore improving the photosensitive significantly. Moreover, the detection efficiency of CuO/PS MSM photodetector was enhanced by ~ 3 times larger than that of the PS-MSM photodetector. The band gap alignment between PS and CuO facilitates the photo induced electron transfer from CuO to PS whereby enhancing the photoresponsivity. The obtained measurements and calculated results have supported the optimum sample for fabricating the best photodetector device.